2013
DOI: 10.1590/s0100-29452013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho da tangerineira 'Span Americana' em diferentes porta-enxertos

Abstract: Este trabalho objetivou avaliar o crescimento vegetativo, a produção e a qualidade de frutos da tangerina 'Span Americana' em diferentes porta-enxertos, nas condições edafoclimáticas de Bebedouro-SP. O plantio foi realizado em junho de 2003, em espaçamento de 6,0 m x 3,0 m, sendo utilizada irrigação por gotejamento a partir de 2006. Os porta-enxertos avaliados foram: citranges [Citrus sinensis (L.) Osbeck × Poncirus trifoliata L. Raf] 'Carrizo' e 'Troyer', tetraploides; trifoliatas (P. trifoliata) 'Davis A' e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
1
14
2
Order By: Relevance
“…For Span Americana tangerine, although an effect of The reduction in vegetative growth of Ponkan tangerine and Folha Murcha orange plants grafted onto Volkamer has also been seen when compared to rootstocks such as Rugoso lemon and Cleopatra tangerine in northwest Paraná state, Brazil (Stenzel et al, 2003(Stenzel et al, , 2005). However, in most studies trees on Flying Dragon had smaller canopies compared to those on Volkamer (Espinoza-Nuñez et al, 2011;Gonzatto et al, 2011;Mademba-Sy et al, 2012;Silva et al, 2013), differently from what we observed (Table 1).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…For Span Americana tangerine, although an effect of The reduction in vegetative growth of Ponkan tangerine and Folha Murcha orange plants grafted onto Volkamer has also been seen when compared to rootstocks such as Rugoso lemon and Cleopatra tangerine in northwest Paraná state, Brazil (Stenzel et al, 2003(Stenzel et al, , 2005). However, in most studies trees on Flying Dragon had smaller canopies compared to those on Volkamer (Espinoza-Nuñez et al, 2011;Gonzatto et al, 2011;Mademba-Sy et al, 2012;Silva et al, 2013), differently from what we observed (Table 1).…”
Section: Resultscontrasting
confidence: 99%
“…The reduced vegetative growth of Lee grafted onto Flying Dragon is consistent with known characteristics as a dwarfing rootstock (Castle, 1978;Cheng & Roose, 1995). This dwarfing effect of Flying Dragon was also observed in many varieties of tangerines, oranges, lemons, and Tahiti lime, in several environmental conditions (Cantuarias-Avilés et al, 2010Gonzatto et al, 2011;Mademba-Sy et al, 2012;Silva et al, 2013).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…This value was significantly higher than those for plants grown on 'Swingle' citrumelo and 'Cleopatra' and 'Sunki' mandarin rootstocks (Table 6). Stuchi et al (2002) and Silva et al (2013) found no significant differences in the technical indices of the fruits from 'Valência' orange and 'Span Americana' (C. reticulata Blanco) mandarin trees grown on different rootstocks, whereas Stenzel et al (2005b) found that the technical index was higher for the fruits from 'Folha Murcha' orange plants grafted on the 'Sunki' mandarin rootstock. These results highlight the importance of the evaluation of the scion-rootstock combinations for local conditions because of the combined effect of genotype interactions and adaptation to edaphoclimatic conditions.…”
Section: Fruit Qualitymentioning
confidence: 99%